Cloning, characterisation and tissue distribution of an aquaporin-3 cDNA from fish (Sparus aurata) - Santos, CRA (2001)
The major intrinsic protein (MIP) family consists of several transmembrane channel proteins specific for water and neutral solutes. All proteins belonging to the MIP family evolved from two divergent bacterial paralogues, one giving rise to the CHIP group, functionally characterised as water channels and the other to the GLP group, specialised in glycerol transport. Three forms of MIP proteins belonging to the GLP group have been identified in mammals: aquaporin-3 (AQP-3), aquaporin-7 (AQP-7) and aquaporin-9 (AQP-9). We have recently cloned and characterised a GLP cDNA from the marine teleost sea bream (Sparus aurata) and studied its tissue distribution. Phylogenetic analysis revealed it was most like AQP-3 and further studies are now underway to determine its role in hydromineral balance.